منهج التفريق اللغوي بين المصطلحات القرآنية: دراسة تحليلية = The linguistic method of differentiation between Quranic terms: an analytical study - Saleem, Wahab; Elatrash, Radwan Jamal Yousef (IIUM Press, 2023)
إن توظيف التفريق اللغوي من أهم المناهج التفسيرية التي اعتمد عليها الصدر الأول، فله حضور ملاحظ في تفاسير الصحابة والتابعين، ولكن هذا المنهج لا يزال مغمورًا بين الباحثين، ومن ثم فهو بحاجة إلى مزيد دراسة وإبراز، وقد أدى غموره بعضَهم إلى زعم أن الاستفادة من الفروق اللغوية في التفسير متكلف ودخيل، وهذا البحث يعالج هذا الإشكال مؤصلًا أدلةَ مراعاة الفروق اللغوية في التفسير خلال الآيات القرآنية والأحاديث النبوية، وآثار الصحابة والتابعين التفسيرية، ونظرًا لطبيعة البحث، فإنه قد انتهج المنهج الاستقرائي والتحليلي لتأصيل كون الفروق اللغوية من أهم الأدوات التفسيرية التي استفاد منها المفسرون القدامى، وذلك من أجل الوصول إلى نتائجَ مهمة، منها على سبيل المثال: إن التفريق اللغوي هو منهج قرآني بالمقام الأول فإن القرآن يوجه الناس إلى التفريق اللغوي؛ ومنها: أنه منهج نبوي في التفسير وفي اللغة عمومًا، كما أن التفريق اللغوي من أهم مناهج التفسير بالمأثور وله حضور بين في تفاسير الصدر الأول. Employing the linguistic method of differentiation is one of the most important tafsir approaches to tafsir used by early scholars. This method was evidently present in the early attempts at tafsir by the companions and their followers. However, the existence of this method in early exegesis remains rather obscure between researchers. This warrants more research to unveil the scope and further extent of its application. The obscurity of this methodology has led some to question the importance of its application or even consider it foreign to the art of tafsir altogether. This paper tackles this issue by fundamentally establishing the proofs of the importance of the linguistic method of differentiation through the Quranic verses, prophetic traditions, and traditions of the companions and their followers. Considering the nature of the topic at hand, this paper uses the inductive analytical method of research in an attempt to establish the fact that linguistic differentiation was one of the most crucial tools employed by early exegetes. It concludes with various results, among which is the fact that linguistic differentiation is, above all, a Quranic methodology as the Quran guides people to differentiate between similar words. It also concludes that linguistic differentiation is a prophetic methodology in both tafsir and language, just as it is one of the most important methods of tafsir within the athar based approach to tafsir, and it is evidently present in the exegetical reports of early exegetes.